Higher Levels of Income and Education are Associated with More Specialized Sport Participation Behaviors: Results from a Representative Sample of Youth Sport Parents from the United States - Eric G Post; Matthew J. Rivera; Darleesa Doss; Lindsey E. Eberman (North American Sports Medicine Institute, 2023)
# Background While previous studies have examined the impact of family socioeconomic characteristics on a child's sport specialization behaviors, this research has been limited to affluent communities with limited sociodemographic diversity. # Hypothesis/Purpose The purpose of this study was to examine associations of parent income and education with child sport specialization behaviors among a nationally representative sample of youth sport parents in the United States. # Study Design Cross-sectional. # Methods Parents of youth athletes in the United States (n=236, age: 39.2±8.1 years, 57.2% female) were recruited to complete an online questionnaire by Qualtrics Online Samples (Qualtrics, Provo, UT) using a combination of actively managed, double-opt-in market research panels. The questionnaire used for this study consisted of: 1) parent demographics (including parent age, race/ethnicity, biological sex, gender identity, household income, and educational status), and 2) child sport participation characteristics and sport specialization behaviors. # Results Parents who reported an annual household income of \$75,001 or more were more likely than parents making less than \$75,000 to report that their child participated on an organized club team (OR \[95%CI\]: 1.94 \[1.15-3.27\]), participated on multiple organized teams at the same time (OR \[95%CI\]: 1.85 \[1.10-3.11\]), or specialized in a single sport (OR \[95%CI\]: 2.45 \[1.45-4.14\]). Parents who reported receiving a Bachelor's degree or higher were more likely than parents who did not to report that their child participated on an organized club team (OR \[95%CI\]: 3.04 \[1.78-5.18\]), participated on multiple organized teams at the same time (OR \[95%CI\]: 2.42 \[1.43-4.10\]), or specialized in a single sport (OR \[95%CI\]: 1.94 \[1.15-3.26\]). # Conclusions Thes results suggest that in the modern youth sport culture, family resources may serve as a major determining factor in the type of experiences available for a youth athlete. # Level of Evidence III